Prognosis for Cutaneous Melanoma by Clinical and Pathological Profile: A Population-Based Study - Buja, Alessandra; Bardin, Andrea; Damiani, Giovanni; Zorzi, Manuel; De Toni, Chiara; Fusinato, Riccardo; Spina, Romina; Vecchiato, Antonella; Del Fiore, Paolo; Mocellin, Simone; Baldo, Vincenzo; Rugge, Massimo; et al. (Frontiers in Oncology, 2021)
Introduction Among white people, the incidence of cutaneous malignant melanoma (CMM) has been increasing steadily for several decades. Meanwhile, there has also been a significant improvement in 5-year survival among patients with melanoma. This population-based cohort study investigates the five-year melanoma-specific survival (MSS) for all melanoma cases recorded in 2015 in the Veneto Tumor Registry (North-Est Italian Region), taking both demographic and clinical-pathological variables into consideration. Methods The cumulative melanoma-specific survival probabilities were calculated with the Kaplan-Meier method, applying different sociodemographic and clinical-pathological variables. Cox’s proportional hazards model was fitted to the data to assess the association between independent variables and MSS, and also overall survival (OS), calculating the hazard ratios (HR) relative to a reference condition, and adjusting for sex, age, site of tumor, histotype, melanoma ulceration, mitotic count, tumor-infiltrating lymphocytes (TIL), and stage at diagnosis. Results Compared with stage I melanoma, the risk of death was increased for stage II (HR 3.31, 95% CI: 0.94-11.76, p=0.064), almost ten times higher for stage III (HR 10.51, 95% CI: 3.16-35.02, p<0.001), and more than a hundred times higher for stage IV (HR 117.17, 95% CI: 25.30-542.62, p<0.001). Among the other variables included in the model, the presence of mitoses and histological subtype emerged as independent risk factors for death. Conclusions The multivariable analysis disclosed that older age, tumor site, histotype, mitotic count, and tumor stage were independently associated with a higher risk of death. Data on survival by clinical and morphological characteristics could be useful in modelling, planning, and managing the most appropriate treatment and follow-up for patients with CMM.